BIMBINGAN KELOMPOK DENGAN TEHNIK PROBLEM SOLVING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMK BINA PUTRA - antika sari, sindy; Masyita Suherman , Maya; Pahlevi, Reza (IKIP Siliwangi, 2025)
This research examines the effectiveness of group counseling using problem-solving techniques to enhance the self-confidence of 10th-grade students at SMK Bina Putra. The study aims to determine the impact of group counseling with problem-solving techniques on the self- confidence of these students. The research employed a one-group pre-test and post-test design. The sample consisted of six 10th-grade students majoring in Electrical Engineering. The study found an increase in students' self-confidence, as indicated by the average pre-test score of 136.83, which rose to an average post-test score of 171.50 after the intervention. Additionally, the T-test results showed a value of 0.005, which is smaller than 0.05, indicating a significant difference between the pre-test and post-test results. This implies that the null hypothesis (Ho) is rejected and the alternative hypothesis (Hi) is accepted. Therefore, it can be concluded that group counseling using problem-solving techniques significantly affects students' self- confidence.